Participation of the SCO in Peacekeeping Activities, Prevention and Settlement of Conflicts - K. M. Barskiy (Vestnik MGIMO-Universiteta)
Abstract: Shanghai Cooperation Oprganization is a multi-functional interstate regional organizaton. One of the main priorities in the activities of the SCO is a cooperation in providing regional security and stability in the areas of counteraction against terrorism, separatism, extremism, drug tarfficking, other types of trans-border organized crime and against use of information-communication technologies in destructive purposes. There are all grounds to suppose that in forthcoming years the SCO, especially considering broadening the circle of its permanent state-members, will do some steps in direction of practical application of its latent potential in prevention and settlement of conflicts. Development of the SCO own peacekeeping instruments fully corresponds to the character and scales of security threats and tendencies of their evolution on the modern stage. Such a mechanism in arsenal of the SCO could play deterring role regarding latent local conflicts in its zone of responsibility. Obvious «plus» of involving the SCO in the peacekeeping sphere lays in the fact that its key members China and Russia - both are permamnent members of the UN Security Ciuncil, large powers, possessing serious financial capabilities, military and military-technological resources and rich experience of participation in peacekeeping operations. This is exactly Russia and China who would be able to share main responsibility of organization and financing the SCO peacekeeping operations. Emphasis on promoting settlement of conflicts, peacekeeping and strenhthening of confidence in the military sphere could become one of key vectors of converting the SCO into the regional security community and even become a foundation for the new system of security of Eurasia in the future.